The role of the lead hip in collegiate baseball pitching: Implications for ball velocity and upper-extremity joint moments - Solomito, M. J.; Garibay, E. J.; Cohen, A.; Nissen, C. W. (Journal of Applied Biomechanics, 2024)
Hip flexibility is an important biomechanical factor for a baseball pitcher. However, there have been limited investigations into the association between upper-extremity joint stresses and ball velocity and hip flexibility, as assessed via motion patterns during the pitch. The purpose of this study was to provide a detailed kinematic description of the lead hip during the pitch and determine the association between lead hip motion and both ball velocity and the elbow varus moment. This study was a secondary analysis of the kinematic and kinetic data previously collected on 99 collegiate-level baseball pitchers using standard optoelectronic motion capture. Significant associations were noted between lead hip internal rotation and both peak ball velocity and the elbow varus moment. The data indicated that for every 10° increase in internal lead hip rotation, ball velocity increased by 0.6 m/s (P < .001, r^2 = .26), and the elbow varus moment increased by 5 N·m (P < .001, r2 = .33). The results of this study suggested that internal hip rotation may be an important means of identifying pitchers that may be at risk for future injury.